OTOMASI DYNAMOMETER REM CAKRAM ANALOG KE DIGITAL UNTUK MESIN MOTOR BAKAR 4 LANGKAH - Sumarta, Nixon Wibisono (LPPM Universitas Bina Bangsa, 2024)
Analogue fuel motor engine power measurement device requires long computation time and low accuracy of measurement results. Innovation is needed by utilising digital technology using an automation system so that several variables are measured and computation can be done simultaneously so that it can shorten time and have high accuracy. The purpose of this research is to apply the Arduino microcontroller, speed sensor and weight sensor to the disc brake dynamometer. This research uses an experimental research method which is part of quantitative research, namely a study that makes an equipment installation or a form that describes completely about the system setting or more leads to analysis. The implementation of this research focuses on the use of the Arduino Uno microcontroller, speed sensor and weight sensor in measuring the torque and power of a 4-stroke petrol engine. The dependent variable in the form of load is generated by the braking load read by the load sensor (load cell) which is an independent variable taken from the engine speed of 1500 Rpm, 2000 Rpm, 2500 Rpm, 3000 Rpm and 3500 Rpm read by the speed sensor. The results showed that the rotation sensor and weight sensor were able to provide appropriate input to the Arduino microcontroller so that the reading results could be displayed properly on the monitor screen and in accordance with the expected results. The conclusion of this research is that the Arduino microcontroller, speed sensor and weight sensor have been successfully applied to the disc brake dynamometer which was originally operated analogously